Establishment of porosity and permeability models correlation to validate E.coli Transport to ground water aquifers: Rivers state of Nigeria - Eluozo, Solomon Ndubuisi; Ademiluyi, J. O. (International Journal of Engineering and Technology, 2012)
The evaluation of porosity and permeability models correlation on the migration of e.coli transport in deltaic environment has been assessed. This is to validate the model generated from the experimental analysis in the study location, this model are generated through the experimental results from both parameters, the theoretical values from both parameters confirm that the models generated is a bench mark that can be applied as a design criteria in preventing the migration of e.coli to ground water aquifer, it has also confirm that it plays a major role in fast transport of e.coli in deltaic environment, the figures displayed shows the level of deposition of geological formation in the study area, the study has also explain the migration of the microbes influenced by porosity and permeability, the results from the experiment that generated theoretical values for porosity and permeability were evaluated to see their relationship in terms of influence on the behaviour of the microbial transport as a system known as plug flow. the results has been confirm that without any inhibition from any other deposition, e.coli will be in progressive phase condition, therefore it is advise that the models generated from the study area should be applied in design of bore hole in other to prevent the pollution emanating from e.coli in the study area, finally the relationships verified from the study has a fit to the existing geological history of the study area that is predominant of alluvium deposition, this condition ascertain the reality of the experimental results generated from the study area ,it should be applied to avoid water related diseases and the threat of life